Моделювання та дослідження параметрів QoS в системі розподілу інформації з самоподібним вхідним потоком і обслуговуванням за порядком черги - Лаврів, О. А. (Матеріали п'ятої Міжнародної науково-технічної конференції «Проблеми телекомунікацій». – К.: НТУУ «КПІ». 2011., 2011)
The information distribution system QoS parameters were researched. This research had been made in the self-similarity circumstances of the input traffic. Serving was made in order of the queue. Serving algorithm had been designed for self-similar input traffic.
Keywords: QoS; самоподібний вхідний потоком